YIELD AND BIOMASS QUALITY OF THE WHOLE PLANT OF FOUR MAIZE HYBRIDS FOR SILAGE PRODUCTION - Terzic, Dusanka (Journal on Processing and Energy in Agriculture, 2020)
This paper presents the results of a study on the yields of green matter, dry matter and digestible dry matter of the whole plant of four ZP silage maize hybrids (gown in four different locations in the Republic of Serbia) and the quality of their whole-plant biomass. The results obtained indicate that the highest average yields of green matter (40.4 t∙ha-1), dry matter (14.4 t∙ha-1) and digestible dry matter of the whole plant (8.8 t∙ha-1) were recorded in the ZP 707 hybrid at all four locations considered. The highest average content of lignocellulosic fibres was detected in the ZP 735 hybrid, which also exhibited the lowest dry matter digestibility of the whole plant (57.24 %). The highest average digestibility of dry matter (61.00 %) and NDF (NDFD - Neutral Detergent Fibres Digestibility) (26.20 %) of the whole maize plant was determined in the ZP 707 hybrid, which also had the lowest average content of all lignocellulosic fibres.
Keywords: maize, yield, biomass quality